Spontaneous resolution of asymptomatic hepatic pseudoaneurysm post radiofrequency ablation - Li, Shyan Ch'ng; Estrellita Elena, Mohd Tazuddin; Benny, Young; Ahmad Faizal, Mohd Ali (British Institute of Radiology, 2015)
Radiofrequency ablation (RFA) of a hepatic tumour is an established treatment option with an acceptable complication rate. Formation of a pseudoaneurysm after RFA of liver metastasis is an uncommon complication. We report the case of a 69-year-old female patient developing a hepatic pseudoaneurysm after RFA of liver metastasis. On a follow-up CT scan 6 weeks later, there was spontaneous resolution of the pseudoaneurysm. Hepatic pseudoaneurysms are usually treated owing to the risk of rupture. Invasive procedures or conservative management of an asymptomatic hepatic pseudoaneurysm is still the subject of debate. The spontaneous resolution of a hepatic pseudoaneurysm in our patient suggests that an asymptomatic pseudoaneurysm maybe observed for resolution instead of being treated at presentation.